Development of Graphical User Interface (GUI) for University Student Health Monitoring - Fadzliana Saad; Ismarani Ismail; Muhd Syamir Mohamad (Institute of Advanced Engineering and Science, 2018)
This paper presents the development of GUI to monitor health condition of university students of Universiti Teknologi MARA (UiTM) Shah Alam.